Analisis Kepuasan Pengguna Terhadap Wesbite Layanan Perbaikan Komputer Lev Computer - Pratama, Adhitya Fajar Risqi Djati; Sampetoding, Eliyah Acantha Manapa (Kesatria : Jurnal Penerapan Sistem Informasi (Komputer dan Manajemen), 2025)
Lev Computer is a computer repair service that provides solutions to various problems faced by users. To provide the best possible service, Lev Computer has created a website where users can access information about Lev Computer profiles, available services, facilities, ratings from patients using Lev Computer services, and Lev Computer address if they are interested in repairs. However, for continued growth, the Lev Computer website still needs a lot of optimization. This study aims to assess the level of user satisfaction with the Leave Computer website and what factors influence it. This study uses the System Usability Scale (SUS) and the Unified Theory of Acceptance and Use of Technology 2 (UTAUT2). This study included 100 respondents, namely Lev Computer website users. The survey using the system usability scale method resulted in a score of 68.3. The mean score on the D grading scale falls into the marginal (high) category and is within the excellent range. Meanwhile, the analysis results of the UTAUT2 model show that there are variables that influence user interest, such as the change in effort expectancy. The results of the conducted research show that users are satisfied with the Lev Computer website is considered acceptable by users as a website that can help users, provide convenience, and provide a pleasant experience in using the Lev Computer website.